Some peculiarities of the INR DTL RF system operation at doubling of average FR power level - Feschenko, A.V.; Kvasha, A.I.; Serov, V.L. (Вопросы атомной науки и техники, 2014)
In accordance to the INR linear accelerator project it was foreseen a possibility of the accelerator operation at RF pulse repetition frequencies up to 100 Hz (duty factor 4%). At that repetition frequency accelerator efficiency is no-ticeably increased, as possibility are appeared of simultaneous acceleration of H+ and H- or operation at the isotope complex and physicists. For this reason, in recent years works connected with doubling RF pulse repetition frequency were begun. In the presented paper some additional aspects of INR DTL RF system operation are described, like plate modulator high voltage supply mode of operation; tank frequency control system; series crowbar system; new final and intermediate RF amplifiers.